2022
DOI: 10.1039/d2fo01481e
|View full text |Cite
|
Sign up to set email alerts
|

Maternal propionate supplementation ameliorates glucose and lipid metabolic disturbance in hypoxia-induced fetal growth restriction

Abstract: Intrauterine growth restriction (IUGR), one of the major complications of pregnancy, is characterized by the low-birth weight and results in higher risks for long-term problems including developing metabolic and cardiovascular...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
2
2
0
Order By: Relevance
“…In addition, the top enriched GO terms were immunologically and metabolically relevant, with results for the former similar to previous findings ( Yang et al, 2021 ). These results are consistent with the occurrence of aberrant immune regulation ( Sato, 2022 ) and fatty acid metabolism ( Chen et al, 2022 ) in the pathogenesis of FGR and suggest that placental eccDNA plays a role in FGR. Six of the 10 top differentially abundant placental eccDNA molecules were successfully validated by Sanger sequencing, a non-optimal result but similar to those obtained in previous research ( Kumar et al, 2020 ; Cen et al, 2022 ), which reflects the gap between next-generation sequencing technologies and Sanger sequencing as the traditional gold standard.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the top enriched GO terms were immunologically and metabolically relevant, with results for the former similar to previous findings ( Yang et al, 2021 ). These results are consistent with the occurrence of aberrant immune regulation ( Sato, 2022 ) and fatty acid metabolism ( Chen et al, 2022 ) in the pathogenesis of FGR and suggest that placental eccDNA plays a role in FGR. Six of the 10 top differentially abundant placental eccDNA molecules were successfully validated by Sanger sequencing, a non-optimal result but similar to those obtained in previous research ( Kumar et al, 2020 ; Cen et al, 2022 ), which reflects the gap between next-generation sequencing technologies and Sanger sequencing as the traditional gold standard.…”
Section: Discussionsupporting
confidence: 87%
“…Bacteroidota abundantly produce propionate, a precursor in glucose, lipid, and protein synthesis. This metabolic activity is believed to contribute to improved fetal growth and plays a role in mitigating glucose and lipid disorders in metabolic diseases [66,67]. We confirmed that the microbiome was transferred from sows to piglets and was retained until the post-weaning period.…”
Section: Discussionsupporting
confidence: 67%
“…It has been reported that SCFAs may regulate intestinal immunity via the production of interleukin-22 by innate lymphoid cells and CD4 + T cells ( 27 ). In a recent study, supplementation of SCFAs, particularly propionate, was shown to reverse the reduction in birth weight in hypoxia-induced FGR ( 28 ). In line with these findings, our data showed that the abundance of SCFA producers Ruminococcaceae , Bacteroides uniformis , and Alistipes onderdonkii was relatively lower, coupled with the involvement of butanoate metabolism in patients with FGR ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%